1989
DOI: 10.1113/jphysiol.1989.sp017545
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic properties of the GABAA receptor main conductance state of mouse spinal cord neurones in culture.

Abstract: SUMMARY1. The kinetic properties of the main conductance state of y-aminobutyric acidA (GABA) receptor channels from somata of mouse spinal cord neurones in cell culture were investigated using patch clamp techniques.2. Whole-cell GABA receptor currents increased in a concentration-dependent manner from 0 5 to 5 /tM. R. L. MACDONALD, C. J. ROGERS AND R. E. TWYMAN suggesting that there was a population of single openings of short duration. The two longest burst time constants were longer than the two longest op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
180
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(205 citation statements)
references
References 29 publications
21
180
2
1
Order By: Relevance
“…However, we found that for each cell type, GABA A R conductance was similar when measured with either mIPSCs or outside-out patch currents (VB: mIPSC, ␥ ϭ 19 Ϯ 1 pS, n ϭ 7; patch, ␥ ϭ 20 Ϯ 1 pS, n ϭ 5; RTN: mIPSC, ␥ ϭ 18 Ϯ 1 pS, n ϭ 6; patch, ␥ ϭ 17 Ϯ 1 pS, n ϭ 5), indicating that similar channels are likely contained at synaptic and somatic sites. These results are consistent with a previous study using single-channel recording tech- niques (Browne et al, 2001), which also found similar GABA A R conductance in RTN and VB neurons, and all values are within the range commonly obtained for GABA A Rs (Macdonald et al, 1989). Additionally, the unitary conductance and number of channels can also be used to calculate the peak open probability (P o-max ) at the maximal current amplitude, a general indicator of the gating efficacy.…”
Section: Nonstationary Variance Analysis Of Mipscs and Outside-out Pasupporting
confidence: 91%
“…However, we found that for each cell type, GABA A R conductance was similar when measured with either mIPSCs or outside-out patch currents (VB: mIPSC, ␥ ϭ 19 Ϯ 1 pS, n ϭ 7; patch, ␥ ϭ 20 Ϯ 1 pS, n ϭ 5; RTN: mIPSC, ␥ ϭ 18 Ϯ 1 pS, n ϭ 6; patch, ␥ ϭ 17 Ϯ 1 pS, n ϭ 5), indicating that similar channels are likely contained at synaptic and somatic sites. These results are consistent with a previous study using single-channel recording tech- niques (Browne et al, 2001), which also found similar GABA A R conductance in RTN and VB neurons, and all values are within the range commonly obtained for GABA A Rs (Macdonald et al, 1989). Additionally, the unitary conductance and number of channels can also be used to calculate the peak open probability (P o-max ) at the maximal current amplitude, a general indicator of the gating efficacy.…”
Section: Nonstationary Variance Analysis Of Mipscs and Outside-out Pasupporting
confidence: 91%
“…We adopted and optimized the parameters we proposed previously (27) to reproduce the gating properties of declustered synaptic GABA A receptors. Because the concentrations of GABA used in that study were Ͼ30 M, the transitions between singly bound open and desensitized states could not be resolved (49,50). Therefore, the corresponding rate constants were merely adopted from Jones and Westbrook (48).…”
Section: Block Of Gaba-evoked Currents Induced By Prolonged Expomentioning
confidence: 99%
“…Analysis of these results, based on a model that is similar in structure to the Jones-Westbrook model we have used (Macdonald et al, 1989b), suggested a number of possible anesthetic actions: (1) halothane may slow the microscopic agonist unbinding rate, or (2) increase the microscopic agonist binding rate; 3) halothane may alter gating transition rates, to favor entry into the longer duration open state (although it is possible that this effect may be secondary to a slowing of agonist unbinding rate); and (4) the increase in burst duration may result from a decrease in agonist unbinding rate or a decrease in the entry rate into desensitization. Based on these single channel results, it was not possible to distinguish between these possibilities.…”
Section: Comparison With Single Channel Studiesmentioning
confidence: 99%